„Несвятые святые” в рассказах o. Ярослава Шипова (к вопросу об особенностях авторского почерка) - Крылова, Снежана (Studia Rossica Posnaniensia, 2019)
The article analyses the originality of the narrative manner of the contemporary writer Yaroslav Shipov, in whose texts the ideals and spiritual challenge of the heroes and storyteller are always accompanied by a dense network of humor and common nonsense. Conclusions are drawn regarding the reasons for such a strategy. The prose by Shipov, though aimed at finding God’s presence in the world, is stylistically and problematically associated with secular and social literature. It motivates the reader to do self-meditation and intellectual work based on the influence of suggestion.